Under the banner of king death : pirates of the Atlantic, a graphic novel - Lester, David, 1958-; Rediker, Marcus (Beacon Press, 2023)
"Under the Banner of King Death explores the sub-culture and resistance of eighteenth-century pirates, telling the tales of John Gwin, an African American fugitive from bondage in South Carolina; Ruben Dekker, a common seaman from Amsterdam; and Mark/Mary Reed, an American woman who dressed as a man and went to sea"--